Hair Washing Formulations from Aloe elegans Todaro Gel: The Potential for Making Hair Shampoo - Desta Berhe Sbhatu; Goitom Gebreyohannes Berhe; Abadi Gebreyesus Hndeya; Asmael Abdu; Afework Mulugeta; Haftom Baraki Abraha; Micheale Yifter Weldemichael; Hailekiros Tadesse Tekle; Haftay Abadi Gebru; Molla Gereme Taye; Haileselassie Gebremeskel Kidanemariam (Hindawi Limited, 2020)
This study aimed to describe the gross phytochemical constituents of Aloe elegans Todaro gel and evaluate the characteristics and quality of lab-made hair washing formulations prepared from the gel to show its potential in formulating hair washing shampoos. A. elegans gel mass was prepared from mature, healthy leaves collected from natural stand. Samples of 100% methanol extract of the gel were subjected to standard phytochemical screening and gas chromatography-mass spectroscopy (GC-MS) analysis. Five hair washing formulations (Fs) were, likewise, prepared by mixing 4.0-10.0 mL of gel with one (0.05 mL) to two (0.10 mL) drops of six synthetic and natural ingredients, namely, coconut oil, jojoba oil, olive oil, pure glycerin oil, lemon juice, and vitamin E. The gel to the total ingredient ratios (v/v) of the five formulations were 93 : 7 (F1), 94.5 : 5.5 (F2), 96.4 : 3.6 (F3), and 96.6 : 3.4 (F4 and F5). The formulations were evaluated using sensory inspection and common physicochemical methods. The phytochemical screening and GC-MS analysis revealed that A. elegans gel is the source of important chemical constituents used in the formulation of shampoos and similar products including saponins, capric acid, lauric acid, myristic acid, palmitic acid, linoleic acid, stearic acid, and phytol. Lab-made A. elegans hair washing formulations, especially those with 96.4-96.6% gel, were found to have similar characteristics and qualities with a common marketed shampoo. All the formulations were turbid with characteristic odor as the marketed shampoo. The pH values of the hair washing formulations (6.4-4.6) were comparable to those of the marketed shampoo (6.7). Formulations with higher proportion of gel had better foam stability, higher solid content (26-29%), higher surface tension (33-38 dynes/cm), shorter wetting time (150-160 sec), equivalent viscosities (26.45-26.73 poise), and conditioning performance than the marketed shampoo. These findings demonstrate that A. elegans gel mass can be used in the formulation of good-quality hair washing shampoos. We recommend future studies that aim to develop the phytochemical profile of the plant and a refined protocol of hair washing shampoo formulation.